Efektivitas Penerapan Kurikulum Merdeka Dalam Mewujudkan Pendidikan Berkualitas di Sekolah Dasar: Dampak dan Tantangan - Santoso, Luhur Pujo; Nugraheni, Nursiwi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The Kurikulum Merdeka is a curriculum innovation that provides freedom to schools, teachers, and students in creating a more adaptive, relevant, and meaningful learning experience as an effort to overcome the learning loss crisis after the Covid-19 pandemic. This study aims to examine the effectiveness of the implementation of the Kurikulum Merdeka in realizing quality education in elementary schools, with a focus on the impact and challenges that need to be overcome. The method used is a literature study by searching for relevant literature sources through Google Scholar. The results of the study show that the implementation of the Kurikulum Merdeka in elementary schools has great potential to improve the quality of education in Indonesia. The success of the implementation of the Kurikulum Merdeka is highly dependent on the availability of resources, infrastructure, the readiness of educators, and synergy between schools and other stakeholders. Optimizing the implementation of the Kurikulum Merdeka requires continuous support from the government in providing facilities, teacher training, and strengthening collaboration between schools, parents and the community.